2017
DOI: 10.1016/j.bmcl.2017.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Novel 1,2-dihydroquinazolin-2-ones: Design, synthesis, and biological evaluation against Trypanosoma brucei

Abstract: In 2014, a published report of the high-throughput screen of >42,000 kinase inhibitors from GlaxoSmithKline against T. brucei identified 797 potent and selective hits. From this rich data set, we selected NEU-0001101 (1) for hit-to-lead optimization. Through our preliminary compound synthesis and SAR studies, we have confirmed the previously reported activity of 1 in a T. brucei cell proliferation assay and have identified alternative groups to replace the pyridyl ring in 1. Pyrazole 24 achieves improvements i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
0
10
1
Order By: Relevance
“…Thus, the EC 50 (50% efficacy concentration) ranged from 1.70 ± 0.19 nM for T. brucei rhodesiense , 2.61 ± 0.08 nM for T. brucei gambiense to 3.12 ± 0.15 nM for T. brucei brucei S16. By contrast, we did not observe any cytotoxic effect against MRC-5 (control), a non-tumoral human cell line extensively used as a control of drug toxicity ( De Rycker et al, 2013 ; Sánchez-Fernández et al, 2015 ; Belmonte-Reche et al, 2016 ; Pham et al, 2017 ), at 12.5 μM AS-48, whereas only 22% growth inhibition was described at 50 μM AS-48 in the murine monocytic cell line Raw 264.7 ( Abengózar et al, 2017 ). The selectivity index of AS-48 was therefore higher than 1.6-3 × 10 4 fold.…”
Section: Resultscontrasting
confidence: 75%
“…Thus, the EC 50 (50% efficacy concentration) ranged from 1.70 ± 0.19 nM for T. brucei rhodesiense , 2.61 ± 0.08 nM for T. brucei gambiense to 3.12 ± 0.15 nM for T. brucei brucei S16. By contrast, we did not observe any cytotoxic effect against MRC-5 (control), a non-tumoral human cell line extensively used as a control of drug toxicity ( De Rycker et al, 2013 ; Sánchez-Fernández et al, 2015 ; Belmonte-Reche et al, 2016 ; Pham et al, 2017 ), at 12.5 μM AS-48, whereas only 22% growth inhibition was described at 50 μM AS-48 in the murine monocytic cell line Raw 264.7 ( Abengózar et al, 2017 ). The selectivity index of AS-48 was therefore higher than 1.6-3 × 10 4 fold.…”
Section: Resultscontrasting
confidence: 75%
“…Some studies reported that quinazolin-2(1H)-ones can be obtained by cyclization reactions using amino acetophenones 25,43,44 or aminobenzonitriles. 45 Our studies on the construction of benzoquinazolinone systems using N-Boc 2naphthylamine derivatives showed that, when a solution of 5a in acetic acid was treated with a large excess of potassium cyanate, the methylbenzoquinazolinone (22a) can be produced in a satisfactory yield (50%, Scheme 6). In addition, when ammonium acetate was added to the reaction mixture, the yield of lactam 22a increased up to 65%.…”
Section: Resultsmentioning
confidence: 99%
“…The cytotoxicity of the compounds that showed an IC 50 value of less than 5 μM was also evaluated against MRC-5, a nontumor human lung fibroblast cell line widely used as a control for drug toxicity. 29,31,32 The selectivity indices (SI) were calculated with the formula IC 50 (MRC-5)/IC 50 (T. brucei). The activity gain (AG) of each compound with respect to HT (1) was calculated according to the formula IC 50 (HT)/IC 50 (compound).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The trypanocidal activity and cytotoxicity of the set of hydroxytyrosol ω-hydroxyalkylcarbonate derivatives 4a – d , 5a – d , 6a – d , and 7a – d and several hydroxytyrosol alkylcarbonate derivatives ( 8c , 8e , 9a – h , 10 , and 11 ) were evaluated in vitro against T. brucei bloodstream forms to calculate the IC 50 (50% inhibition of parasite growth). The cytotoxicity of the compounds that showed an IC 50 value of less than 5 μM was also evaluated against MRC-5, a nontumor human lung fibroblast cell line widely used as a control for drug toxicity. ,, The selectivity indices (SI) were calculated with the formula IC 50 (MRC-5)/IC 50 ( T. brucei ). The activity gain (AG) of each compound with respect to HT ( 1 ) was calculated according to the formula IC 50 (HT)/IC 50 (compound).…”
Section: Resultsmentioning
confidence: 99%